Outcome of pregnancy in patients with systemic lupus erythematosis at Korle-bu Teaching Hospital - Dey, I.D.; Coleman, J.; Kwarko, H.; Mate-Kole, M. (Ghana Medical Journal, 2016)
Objective: To study maternal and fetal outcomes in Ghanaian women with systemic lupus erythematosus (SLE). Methods: Retrospective study of pregnancies in women with SLE in a single centre in Ghana. Results: The mean age was 30.1 years and all were nulliparous. Two out of the seven pregnancies were in disease remission at the time of booking. Nephritis without renal impairment was present in 7 pregnancies (6 women). One woman developed intrapartum eclampsia. Two women had secondary antiphospholipid syndrome (APS). Two suffered early fetal losses and one late fetal loss at 32 weeks. All three who lost their fetus had uncontrolled hypertension. Six had mild flares mainly joint pains during pregnancy. There was no maternal mortality. The median gestational age at delivery was 38 weeks (range, 16 to 40 weeks) and the mean birth weight was 3017 g; the median Apgar scores were 8 and 9 at 1 and 5 minutes of life, respectively. There were no cases of intrauterine growth restriction (IUGR). There were no cases of congenital heart block or neonatal lupus. Conclusion: Good pregnancy outcomes are possible in women with SLE even in resource poor settings. . All pregnancies should still be considered high risk and be managed jointly between the obstetricians, the perinatologists and the rheumatologists, in particular, those with renal involvement and hypertension. Long term follow up of a larger cohort is needed.
Journal Article on regnancy in patients with systemic lupus erythematosis
Keywords: Systemic lupus erythematosus; pregnancy; foetal outcomes; maternal outcomes